The Effect of Average Length of Schooling, Life Expectancy and Economic Growth on Poverty in Banjarnegara Regency 2005-2019 - Sri Sudaryati; Abdul Aziz Ahmad; Suprapto Suprapto (EKO-REGIONAL, 2021)
Banjarnegara Regency is one of the districts in the poverty red zone in the Central Java Province. In 2019, Banjarnegara Regency was in the 7th (seventh) position of the 35 (thirty-five) poorest regencies/cities with a poverty percentage of 14.76%.  This study purpose to analyze the effect of the average length of schooling, life expectancy and economic growth in the agriculture, fisheries and forestry sectors on poverty in Banjarnegara Regency in 2005-2019. The variables used are the average length of schooling, life expectancy and economic growth in the agricultural, forestry and fisheries sectors. The data used in this study is secondary data obtained from the Statistics Central Agency of Banjarnegara Regency. The results of this study are the average length of schooling and life expectancy have a negative and significant effect on poverty, while the economic growth in the agriculture, forestry and fisheries sectors does not have a significant effect on poverty. The implication of this research is that the local government of Banjarnegara Regency needs more intensive efforts from the local government to increase development in the education and health sectors with the expectation of encouraging wider learning opportunities, upraising education levels, and improving the quality of health of the population. Keywords: Poverty, Average Length of Schooling, Life Expectancy, Economic Growth in The Agricultural, Forestry and Fisheries Sectors